The Green-Hushing Paradox: A Systematic Review of Strategic Silence and Its Impact on Brand Authenticity and Consumer Trust - Selamet Agung Santoso; Isnaini Hani'ah (Journal of Marketing Breakthroughs, 2026)
Objective:  This study aims to examine the phenomenon of green-hushing, defined as the strategic reduction of sustainability communication despite the continued implementation of environmental practices, and to analyze its driving factors and implications for brand authenticity and consumer trust amid an increasingly closely scrutinized ESG environment. Research Design & Methods: This study employs a Systematic Literature Review (SLR) method following the PRISMA 2020 protocol and the SPAR-4-SLR framework. A total of 194 articles from Q1-ranked journals and global industry reports published between 2015 and 2026 were analyzed. The data were synthesized using a thematic approach to identify patterns related to strategic communication, consumer perceptions, and institutional pressures. Findings: The findings indicate that “green-hushing” practices emerge as a strategic response to regulatory pressures, litigation risks, and growing skepticism toward sustainability claims. However, reduced communication is consistently associated with lower perceptions of transparency, which undermines brand authenticity and ultimately erodes consumer trust. The study’s results also reveal a paradoxical effect, whereby efforts to mitigate reputational risk through silence may actually trigger negative conclusions from consumers and reduce market confidence. Contribution: This study contributes to the body of knowledge by extending signaling theory into the context of absent or reduced communication, and by conceptualizing “green-hushing” as a form of strategic signal withdrawal. It also integrates insights from sustainability communication and consumer behavior to explain how reduced transparency influences trust formation. Novelty: This study introduces the concept of the “Sustainability Gap,” which describes the mismatch between actual environmental performance and public perception due to a lack of communication. It also proposes a conceptual framework linking “green-hushing” practices, transparency, brand authenticity, and consumer trust.